Spatiotemporal dynamics in silver thiosulfate, silver sulfide reaction-diffusion system - Badr, Layla (Frontiers in Physics, 2026)
Liesegang pattern formation is a self-organizing phenomenon governed by diffusion and reaction kinetics generally in a porous matrix. This study investigates the transient precipitation dynamics of silver thiosulfate and its subsequent formation into silver sulfide Liesegang pattern within gelatin matrices through the diffusion of sodium thiosulfate into silver nitrate. The interplay between the decomposition of Ag2S2O3 to Ag2S and its dissolution into soluble [Ag(S2O3)2]3- complex ion under excess thiosulfate produces Ag2S periodic patterned bands. The migration extent of the Ag2S2O3 band increases with increasing concentration gradient and its width increases with increasing gelatin percentage. The Ag2S bands morphology and clarity are primarily regulated by the gelatin structure and solvent polarity, with potassium fluoride, an inert salt contributing to sharper boundaries through increased complex ion and colloid stability. The system successfully isolates the thermodynamically unstable silver thiosulfate, produces in some cases equidistant silver sulfide Liesegang pattern for the 2.5% gelatin systems, and reveals that pattern morphology and spacing can be tuned by modifying experimental conditions. In addition, this study is significant for understanding a unique class of Liesegang patterns wherein the kinetics of dissolution and dissociation are alternating in response to the diffusion of a counter ion that initially forms a precipitate at the reaction front.